2019
DOI: 10.1177/1367006919846426
|View full text |Cite
|
Sign up to set email alerts
|

Polysyllabic shortening in Spanish-English bilingual children

Abstract: Aims and objectives: Polysyllabic shortening is thought to contribute to the perception of stress-timed rhythm in some languages. Little is known about its use in the speech of children exposed to a language that incorporates it more frequently (e.g. English) and one that incorporates it less frequently (e.g. Spanish). The purpose of the current investigation was to explore polysyllabic shortening in bilingual children’s two languages compared to monolingual Spanish and English comparison groups. Method/Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Moreover, the present study's findings do not agree with Gibson and Bernales (2019), who argued that PS could arise from a universal phonetic constraint that requires a faster articulation rate the more syllables are added and that it is not strongly related to language proficiency. The slightly better performance of the advanced group (although statistically not significant except for foot duration) seems to suggest that more experience with the language may have a positive effect on the acquisition of timing properties of the English rhythm.…”
Section: Percentages Of the Long Vowel In The Whole Wordcontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, the present study's findings do not agree with Gibson and Bernales (2019), who argued that PS could arise from a universal phonetic constraint that requires a faster articulation rate the more syllables are added and that it is not strongly related to language proficiency. The slightly better performance of the advanced group (although statistically not significant except for foot duration) seems to suggest that more experience with the language may have a positive effect on the acquisition of timing properties of the English rhythm.…”
Section: Percentages Of the Long Vowel In The Whole Wordcontrasting
confidence: 99%
“…In another study tackling PS among bilingual children, Gibson & Bernales (2019) compared PS in Spanish and English bilingual children with that in monolingual Spanish and English ones. They found that both groups implemented PS similarly although Spanish is syllable-timed, while English is stress-timed.…”
Section: Introductionmentioning
confidence: 99%